Magwee / Manyue (满月): Sebuah Inkulturasi Ritual Kelahiran dalam Tradisi Umat Katolik Tionghoa - Arief Gunawan (Sekolah Tinggi Filsafat Seminari Pineleng, 2022)
This paper discusses the ritual of Magwee or Manyue, a celebration of the first month for babies in Chinese tradition. The purpose of this essay is to find the theological meaning behind the Chinese ritual and at the same time to work out a model of inculturation of the Christian faith. The paper uses a qualitative approach with interpretative phenomenological analysis (IPA). The author finds the possibility of inculturating faith and liturgical inculturation based on the Magwee ritual. The essence of the Magwee ritual as a celebration of gratitude for the newborn is maintained, but this ritual needs to be placed in the context of the liturgical celebration of the Catholic Church. In the context of inculturating faith, the Magwee ritual needs to be reflected in the light of the Bible. The Magwee Ritual is not just a traditional ritual but reaches its fullness in the spirit of Christ.